Manajemen Risiko Keselamatan dan Kesehatan Kerja (K3) dalam Pelaksanaan Proyek Konstruksi di Muara Sabak - Eka Pratama Puteri; Elvira Handayani; Ria Zulfiati; Annisaa Dwiretnani; Wari Dony (Universitas Batanghari Jambi, 2023)
Risk Management Of Occupational Safety And Health (K3) In Construction Project Implementation In Muara Sabak aims to find out how the implementation of K3 and identify the K3 risks that exist in the project as well as to control the risks. In this construction project, the researcher only reviewed the AC-WC layer work. The results of this study obtained risk levels for AC-WC layer work are classified as very high risk as much as 10%, high risk as much as 40% and medium risk as much as 50%. The appraisal method that reseacher used is Matrix risks scouring by AS/NZS 4360 : 2004.